Nucleotide sequences of chimpanzee MHC class I alleles: evidence for trans-species mode of evolution. - Mayer, W E (1988)
To obtain an insight into the evolutionary origin of the major histocompatibility complex (MHC) class I polymorphism, a cDNA library was prepared from a heterozygous chimpanzee cell line expressing MHC class I molecules crossreacting with allele-specific HLA-A11 antibodies. The library was screened with human class I locus-specific DNA probes, and clones encoding both alleles at the A and B loci have been identified and sequenced. In addition, the sequences of two HLA-A11 subtypes differing by a single nucleotide substitution have been obtained. The comparison of chimpanzee and human sequences revealed a close similarity (up to 98.5%). The chimpanzee A locus alleles showed greatest similarity to the human HLA-A11/A3 family of alleles, one of them being very close to HLA-A11. Similarly, segments of the ChLA-B alleles displayed greatest similarity to certain HLA-B alleles. The calculated evolutionary branch point for the A11-like alleles is 7 x 10(6) to 9 x 10(6) years, whereas the other A locus alleles diverged between 12 x 10(6) and 17 x 10(6) years ago. Since the human and chimpanzee lineages separated 5 x 10(6) to 7 x 10(6) years ago, our data support the notion that during evolution, MHC alleles are transmitted from one species to the next.